SOCIAL RESEARCH METHODS : Qualitative, Quantitative and Mixed Methods Approaches - Gronmo, Sigmund (SAGE Publications Ltd, 2024)
Framing research as the process of asking and answering questions, this book demonstrates how to identify good research questions and how to structure and explore them successfully. Whether you are just beginning your research journey or are a seasoned traveller, it helps you: Decide what you want to achieve with your research Know what options you have to explore your goals Navigate the nuances of different research approaches Understand the decisions of other researchers Choose what path best suits your project. Through real-life examples demonstrating different types of research, the book introduces qualitative, quantitative, and mixed methods approaches so you can compare different methods at every stage of the research process, from initial idea and design to data collection and analysis